2004
DOI: 10.1007/s00127-004-0739-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban regeneration and mental health

Abstract: The urban regeneration initiative may have had little impact because it failed to address the concerns of local residents and failed to remove restricted opportunities, which appeared to be the key factor. A longer follow-up period may be required to demonstrate an effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 1 publication
2
38
1
Order By: Relevance
“…Although the low response rate (17%) might have affected the generalisability of results, it is likely that the results are representative [23,24] because the resulting sample closely matched demographically the population from which it was derived [27], life circumstances were representative of those reported for similar deprived areas [28] and subjective QOL ratings were in accordance with those of national, representative household samples [29] when age and deprivation were accounted for; follow-up rates were also reasonable in healthy population (52%) and CMD (46%) groups. The data presented here are restricted to community dwelling adults aged 18-65.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the low response rate (17%) might have affected the generalisability of results, it is likely that the results are representative [23,24] because the resulting sample closely matched demographically the population from which it was derived [27], life circumstances were representative of those reported for similar deprived areas [28] and subjective QOL ratings were in accordance with those of national, representative household samples [29] when age and deprivation were accounted for; follow-up rates were also reasonable in healthy population (52%) and CMD (46%) groups. The data presented here are restricted to community dwelling adults aged 18-65.…”
Section: Methodsmentioning
confidence: 94%
“…This study involved secondary analysis of data derived from two studies -a community survey examining the QOL and mental health outcomes of urban regeneration [23,24] and Manchester site data from the UK700 randomised control trial of case management [25]. Objective life-conditions, life-opportunities and subjective QOL were assessed at two time-points, using the same methods in the three mental health-status groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the urban regeneration initiatives may have had little impact on mental health because it failed to address the concerns of local residents, and failed to remove restricted opportunities, a variable closely related to mental health (Huxley et al, 2004). E c o n o m i c i m p a c t s a n d u r b a n r e g e n e r a t i o n Closely associated with mental and physical health are economic issues which have various health implications for urban regeneration projects.…”
Section: H E a L T H A N D S O C I A L E F F E C T S O F H O U S I N mentioning
confidence: 87%
“…Psychosocial changes associated with these improvements were found to: reduce anxiety and depression, improve self-esteem, reduce fear of crime and create a greater perceived "friendliness" of the area (Curtis et al, 2002). However, a longitudinal study of an urban regeneration project in South Manchester, England found no improvement over time in mental health for those in the area undergoing urban regeneration (Huxley et al, 2004).…”
Section: H E a L T H A N D S O C I A L E F F E C T S O F H O U S I N mentioning
confidence: 96%